'The fire rises': identity, the alt-right and intersectionality. Issue 2 (4th May 2018) - Gray, Phillip W.
Abstract: This article examines the ideology of the 'alt-right, ' specifically in its relation to the importance of identity. Placing the alt-right within the context of the rising importance of identity within American society, the article discusses the alt-right as overlapping in significant ways with the identitarian elements within the American Left. Investigating the manner in which national/racial identity plays a central role in alt-right thinking and using the notion of 'category-based epistemology' for guidance, this article argues that the alt-right – rather than a quirk of the 2016 electoral cycle – is likely to increase in its importance as a 'rightist' form of intersectionality.